The Geopolitical Presentation of the Cyprus Issue in the Present Conjuncture. - Ioannis Mazis (China Institute for International Strategic Studies Defence Analysis Institute/IAA, 2005)
Concerning the present situation we must bear into mind the following: A) No external mediation can replace the interested parties in a recommencement of talks for a jointly accepted solution in the Cyprus Issue. B) The Turkish occupation troops must withdraw from the Island shortly and certainly before the implementation of the new solution. C) The last wave of Turkish settlers must return to Turkish territories, where it originally came from. D) The complete demilitarization of the Island and its accession to NATO, as the unique reliable figure of regional and international security. This means that Ankara can no longer promote claims of “insecurity” for the Turkish population of the Island. Furthermore it means that the “Sovereign British Bases” have no place in Cyprus. E) In order for all this to be achieved, the government of Athens must not pressure in any way the legitimate Government of the Republic of Cyprus of Mr. Tassos Papadopoulos and it must allow as it has already done in the case or the April 4th Referendum, the Cypriot people to express freely and without bias its opinion. The line of action adopted by Mr. Karamanlis and Mr. Molyviatis in this case must be continued. On the other hand, the talks with the legitimate Cypriot government of the now European Republic of Cyprus for its accession to NATO must begin. This will constitute the most important key-point of the century-old Cyprus Issue.